The Frequency and Sensitivity Pattern of Pseudomonas aeruginosa among Otitis Media patients in Nasiriyah City - Saad; Zahraa (University of Thi-Qar Journal, 2020)
Otitis Media considered as one of the most common types of ear infections, as well as the most blamed etiology is bacterial. Pseudomonas aeruginosa is the most diagnosed pathogens causing these infections. P. aeruginosa has virulence factors that lead to damage to the mucosa of the middle ear. A total of two hundred and ten (210) samples collected from Otitis media patients whom consulting the Ear, Nose, and Throat (ENT) section in AL-Habbobi Teaching Hospital in Al-Nasiriyah City, Southern-Iraq. During the period from August 2018 to January 2019. P. aeruginosa accounted for 65 samples (30.95%). Almost of isolates were sensitive to Carbapenem. The present study concludes females constitute a high percentage of infection with Otitis media (P-value= 0.01) and younger ages are more exposed to the risk of Otitis media (P-value = 0.36). The present study aimed to detect the relationship between the prevalence of Otitis media and the parameters associated with patients like gender, age, housing, and the study period. Also studying the pattern of antibiotics Sensitivity for the targeted bacteria and detection of some virulence factors.